2017
DOI: 10.1111/1475-6773.12651
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation in Utilization of Life‐Sustaining Treatments among Patients with Do Not Resuscitate Orders

Abstract: Hospitals vary widely in the scope of invasive or organ-supporting treatments provided to patients with DNR orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our findings expand upon previous reports in that early DNR use varies widely between hospitals, and is not sufficiently explained by patient comorbidity case mix. 10,12,19,31 Previous work by our study group has demonstrated similar findings for patients with Heart Failure and Pneumonia. Our findings in this study reinforce that DNR status is a strong confounder of hospital mortality metrics.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings expand upon previous reports in that early DNR use varies widely between hospitals, and is not sufficiently explained by patient comorbidity case mix. 10,12,19,31 Previous work by our study group has demonstrated similar findings for patients with Heart Failure and Pneumonia. Our findings in this study reinforce that DNR status is a strong confounder of hospital mortality metrics.…”
Section: Discussionsupporting
confidence: 79%
“…(1)(2)(3)(4) Mechanistically, patient preferences for treatment limitations can be conceptualized as both predictors of mortality risk and effectors of mortality risk. Older patients and patients with preexisting serious illness who are more likely to die with an acute illness are more likely to have treatment limitations.…”
mentioning
confidence: 99%
“…We were able to leverage new ICD-9 codes identifying a representative sample of patients with DNR orders across the United States. Prior studies from the state of California-which routinely collects information on patient DNR status at hospital admission-have shown similarly high levels of hospital variation in DNR orders (9) and inverse associations between hospital DNR rates and use of life-support interventions (but not measures of hospital EOL treatment intensity) among patients with DNR orders (10).…”
Section: Discussionmentioning
confidence: 94%
“…Multiple randomized controlled trials have demonstrated that PCT-based algorithms can substantially reduce antibiotic exposure without increasing mortality or infection-related complications (5)(6)(7)(8)(9). These have led to clinical practice guidelines suggesting use of PCT to guide antibiotic duration for patients with sepsis or suspected infection (1,10,11).…”
mentioning
confidence: 99%